The embolisation of renals vessels like a part of treatment in patients with renal carcinoma - Jaroń, Bernard; Brzozowski, Krzysztof; Twarkowski, Paweł; Żukowski, Paweł (Contemporary Oncology/Współczesna Onkologia, 2005)
Purpose: In statistical data the frequency of renal carcinoma growth with the human age independent from the region. The renal carcinoma is 3% of all malignant neoplasm. The ambolisation of renal arteries is important element of treatment among patients with renal carcinoma. The aim of this study is to show the applicability of renals artery embolisation before surgical treatment or also in cases of non-operative changes like a paliative treatment. The patient were from urology and oncology clinic. There were 106 patients (30 woman and 76 man, average year 57). In 84 cases we perform the renal artery embolisation before surgical treatment, 22 patient paliative embolisation. In six patient it was necessary to perform second embolisation due to recanalisation of embolisated artery. In 5 patient we embolised the artery of second kidney due to metastases into this organ. The embolisation of renal arteries and the pathological tumours vessels before surgical treatment decrease the risk of bleeding and make easier the surgical procedure. In cases with non-operative changes the embolisation reduce the tumour size and the tumour growth, decrease the pain and elongate the patiens life.